The Influence of Fracturing Fluid Volume on the Productivity of Coalbed Methane Wells in the Southern Qinshui Basin - Wenwen Chen; Xiaoming Wang; Mingkai Tu; Fengjiao Qu; Weiwei Chao; Wei Chen; Shihui Hou (Energies, 2022)
Hydraulic fracturing is the main technical means for the reservoir stimulation of coalbed methane (CBM) vertical wells. The design of fracturing fluid volume (FFV) is mainly through numerical simulation, and the numerical simulation method does not fully consider the water block damage caused by the leakage of fracturing fluid into the reservoir. In this work, the variance analysis method was used to analyze the production data of 1238 CBM vertical wells in the Fanzhuang block and Zhengzhuang block of the Qinshui Basin, to clarify the relationship between the FFV and the peak gas production (PGP) under the different ratios of critical desorption pressure to reservoir pressure (Rc/r), and to reveal the controlling mechanism of fracturing fluid on CBM migration. The results show that both the FFV and Rc/r have a significant impact on gas production. When Rc/r < 0.5, the PGP decreases with the increase of the FFV, and the FFV that is beneficial to gas production is 200–500 m3. When Rc/r > 0.5, the PGP increases first and then decreases with the increase of FFV. Specifically, the FFV that is favorable for gas production is 500–700 m3. Excessive FFV does not significantly increase the length of fractures due to leaks in the coal reservoir. Instead, it is more likely to invade and stay in smaller pores, causing water block damage and reducing gas production. Reservoirs with high Rc/r have larger displacement pressure, which can effectively overcome the resistance of liquid migration in pores, thereby reducing the damage of the water block. Therefore, different reservoir conditions need to match the appropriate fracturing scale. This study can provide guidance for the optimal design of hydraulic fracturing parameters for CBM wells.